Potential and prospects of hydrokinetic energy in Malaysia: A review - Maldar, N.R. (Elsevier Ltd, 2022)
Endlessly rising power demands coupled with the growing urge to tackle the effects of climate change has compelled governments worldwide to explore and utilize every possible clean energy option within their geographical vicinities. Malaysia aims to expand the share of renewables in its installed power generation capacity to 20 by the year 2025. To achieve this target, it is extremely important to carry out consistent advancements by unlocking the yet unexploited sustainable alternatives. This paper addresses the abundantly available hydrokinetic resource around Malaysia, which many researchers have suggested as a potential choice for fulfilling a reasonable proportion of Malaysia's power demand. Since the inception of Malaysian interest in hydrokinetic energy, several studies have been published that focus on identifying the ideal locations across the country for deploying hydrokinetic turbines (HKTs). Through this paper, the authors develop a coherency between those studies and establish a complete picture of the existing literature background on hydrokinetic resource in Malaysia. Such a review is yet to be published and will be a crucial benchmark, especially for future researchers who aim to investigate the still unexplored locations. The paper also discusses the resource evaluation techniques adopted by various researchers and highlights the vital considerations that must be accommodated in future studies to achieve more accurate assessments. Â© 2022 Elsevier Ltd